Sensor-based weightlifting workout assisting system design and its practical implementation - Luzar, M.; Czajkowski, A.; Kasperowicz, R.; Rot, M.; Semegen, M.; Korbicz, J. (Journal of Sensors, 2019)
The paper is devoted to the problem of counting repetitions and automatic weight stack detection in a weightlifting machine used for weight training. Some weightlifting machines include a weight stack that can be adjusted by a user. For example, the user can choose to increase or reduce the weight load using the weight stack, thus changing the difficulty level of a particular exercise. Users may want to perform a desired number of repetitions of an exercise or to perform an exercise with a desired range of motion when using such weightlifting machines. From a medical point of view, it is often required that an exact number of repetitions of a given load are performed in order to aid in a prompt recovery. This paper describes a complete design of the system and the algorithm that allows one to collect data from such a machine. Data can then be used for various purposes: in overviews and statistical analysis of a number of workouts. The approach presented in this paper is part of an application for European patent number 18461537.5-1126.